The Concept Of Character Education According To Hamka And Its Relevance To National Education Goals - Y Satria Hafizil Khalil; Emawati Emawati (Yayasan Rahmat Islamiyah, 2026)
This research aims to identify and analyze the values of character education formulated by Hamka, as well as examine the extent to which they are relevant to national education goals. This research uses qualitative research with a Library Research approach. The results of the research show that Hamka's thoughts on character education have relevance to current national education. That national education has the responsibility to prepare a generation to form advanced and civilized Indonesian people. In accordance with the goals of national education in Law no. 20 of 2003, the relevance of the concept of character education according to Hamka as stated in the goals of national education is religious character, honesty, curiosity, reading, respect for achievement, communicative, creative, independent and democratic.